Comparative Effects of Animal and Vegetable Fats on Lipid Profile and Patho-physiological Changes in Mice (Journal of Scientific Research, 2013)
Dietary intake of high amounts of animal fats can cause hypercholesterolemia whereas plant fat like soybean oil reduces serum cholesterol and lipoproteins in mice. The effects of animal fat (butter) and plant fat (soybean oil) fortified diet on lipid profile (serum total cholesterol, low density lipoprotein-cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), and triglycerides), body weight, blood glucose and on tissue texture were investigated in mice. 30 Swiss albino mice were divided equally into three groups. Mice were fed a normal diet (untreated control), a high-fat diet (5% butter) (butter group) and an unsaturated fat diet (5% soybean oil) (soybean oil group) for 90 days. Mice of butter group showed significantly increased level of total cholesterol, LDL-C and triglycerides and decreased level of HDL-C in the serum but not found in mice of soybean fed diet group. Body weight and blood glucose were also markedly elevated in mice fed only butter enriched diet. Histological analysis of liver at the end of 90 days showed increased fat deposition in the mice fed with butter diet than those of control diet and plant fat diet group. Mice fed with butter showed an elevation of lipid levels and developed fatty changes in liver.Keywords: Butter; Soybean oil; Lipid profile; Fatty change; Mice.© 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v5i2.11909        J. Sci. Res. 5 (2), 353-361 (2013)